Using a Structural Equation Model to Evaluate the Roles of Traditional Institutions in Rural Agriculture Success and Sustainability - Ndlovu, Wiseman; Mwale, Marizvikuru; Zuwarimwe, Jethro (Asian Journal of Agriculture and Rural Development, 2022)
Integrating and facilitating effective participation of the Traditional Leadership Institution (TLI) in rural development remains a challenge to date. It remains unclear what the agriculture sector-specific institutional roles are and how they impact the success and sustainability of agriculture. Furthermore, the barriers to institutional effectiveness remain unknown. A structural equation model was used to evaluate the moderating effect of barriers to institutional effectiveness on the relationship between TLI roles and agriculture success and sustainability. ATLAS.ti version 8 and Statistical Package for Social Sciences Amos version 26 were used for the analysis. In the first part of the study, participants’ views on the three variables were explored through focus groups and interviews (N = 103). Next, construct measures for each scenario were modeled in a self-administered survey questionnaire (N = 211). Farmers, traditional leaders, and key informants in the Vhembe and Mopani districts of Limpopo province, South Africa, provided data for the study. It emerged that of the five identified TLI roles, four had a significant impact on the success and sustainability of agriculture projects. Promoting social capital (networks, partnerships, and collaborations) among farmers and development actors had the greatest effect. The barriers to institutional effectiveness were significant and moderated how the TLI influenced rural agriculture success. Resultantly, the impact of institutional contributions on agriculture remained negative despite improved participation by the TLI. Minimizing the effects of the identified barriers while enhancing the institutional capacity to promote the success and sustainability of rural agriculture is recommended.